(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Among people exposed to major psychological stressors in early life, there are elevated rates of morbidity and mortality from chronic diseases of aging. The most compelling data come from studies of children raised in poverty or maltreated by their parents, who show heightened vulnerability to vascular disease, autoimmune disorders, and premature mortality. Movement disorders are common neurologic disturbances in childhood. There are two major types of movement disorders. For the purpose of the study, the investigator selected 142 children’s with movement disorders between the age of 10 to 15. The present study is designed to discover the nature, broaden and correlates of stress experienced by the individuals with movement disorders.